Matching NBP interest rates to different versions of the Taylor rule - Grabia, Tomasz (Olsztyn Economic Journal, 2019)
The interest rate is the basic instrument of monetary policy, directly or indirectly affecting basic macroeconomic variables, such as inflation, unemployment and economic growth. The aim of the article is to compare the NBP reference rate with hypothetical rates calculated on the basis of different variants of the Taylor rule and to indicate which of those variants is best suited to the situation in Poland. The study period of 2000-2017 was adopted for the analysis. On its basis, it was found that in most cases the real interest rate of the central bank in Poland strongly coincided with rates that would have been set if one of the varieties of the Taylor rule had been in force. The best match coincided with the modified version of this rule, which was created after the economic crisis. That means that the NBP took into account both the deviations of inflation from the target and the GDP gap when making decisions regarding interest rates.